Parent engagement with a short, animated storytelling video aimed at reducing stigma towards transgender children and adolescents: Post-trial assessment of a randomized controlled trial - Merlin Greuel; Doron Amsalem; Misha Seeff; Jennifer Gates; Shuyan Liu; Andrés Martin; Till Bärnighausen; Maya Adam (SSM - Mental Health)
Background: Transgender adolescents commonly experience hate speech on social media, contributing to transphobia and adverse health outcomes. While social media can increase polarization and stigma towards vulnerable groups, they may also facilitate intergroup contact. Short, animated storytelling (SAS) videos have shown promising stigma-reducing effects. However, there is scarce evidence on viewers’ engagement with these videos. Objective: This study evaluates the voluntary engagement of 481 US-based parents with a SAS video aimed at reducing stigma towards transgender youth. Methods: 1267 US parents were recruited through the online platform Prolific Academic and randomized into the SAS intervention viewing the video or the control group. The optional, post-trial access to the intervention was available to the control group only. We measured the amount of time subjects in the control group spent voluntarily watching the video and analyzed this data by demographic characteristics and pre-existing transphobia, as measured by the Transgender Stigma Scale (TSS). We used chi-square tests to examine whether subjects’ engagement was associated with sociodemographic factors, and Pearson correlation tests to examine the association between baseline TSS scores and view time. Results: Almost all participants (95%) watched at least 50% of the video, 92% watched at least 75% of the video, 90% watched at least 90% of the video, and 88% watched the entire video. Female subjects and those with low baseline transphobia showed longer view times than male participants and those with high transphobia, respectively. We observed no association between video completion and participants’ age or race/ethnicity. Conclusion: We found significant voluntary engagement with an SAS video aimed at reducing transphobia among US parents. Engagement was high even among those with elevated transphobia. Animations rooted in authentic storytelling may thus bridge user communities with differing ideologies on social media. Future studies should test engagement in real social media environments.